Potato From Incas to All Over the World - Yildiz, Mustafa (IntechOpen, 2018)
Potato is the world's fourth food crop after maize, wheat, and rice and is a staple crop in many diets throughout the world with a high source of proteins, carbohydrates, minerals, and vitamins. Biotic and abiotic stress factors give rise to decrease in yield. That is why improvement of new cultivars resistant to stress factors by conventional and biotechnological methods is extremely important. The most important factor in production increase is the use of healthy seed tubers along with using drought-, heat-, and salt-tolerant cultivars. On the other hand, protection and storage of surplus crops, which are the most important stage in its marketability, are the main problems in potato. In this book, all these issues are discussed, and it is hoped that the book Potato will help growers and researchers in solving problems in potato cultivation.